Effect of the aluminum concentration on the second harmonic generation in a quantum dot of AsGa/AsGa1−xAlx (2022)
The effect of aluminum concentration on the second harmonic generation (SHG) in a cylindrical quantum dot (CQD) is studied theoretically, using the density matrix formalism and a perturbative procedure. The energy levels and wave functions of an electron in the CQD were obtained by solving the time-independent Schrödinger equation in the framework of the effective mass approximation. Numerical calculations are performed for a CQD of GaAs/Al1−xGaxAs. It was found that the increase in the aluminum concentration produces a decrease in the intensity of the SHG and a blue shift in the resonant peaks of the optical res- ponse of the object of study.